Crop-animal systems in Asia: Future perspectives - Devendra, C. (Elsevier, 2002)
In the next two decades, the demand for animal products will more than double. The concluding paper provides some considered predictions on the future for crop animal systems in Asia, as a consequence of this trend. Although meat and eggs from non ruminants in industrial systems will continue to be the main source of animal proteins, it is unlikely that these systems will meet all of the projected demands. The consumption of ruminant meat and milk is increasing in most of Asia, and 95% of ruminants are found in the mixed farming systems. Whilst involution of mixed farming systems is one possible scenario, particularly in the highly populated tropical highlands, it is the opinion of the authors that crop animal systems will see important growth and remain the dominant system in Asia. Mixed farming systems will continue to be the main avenue for intensification of food production, with some specialisation in crop or animal activities. In addition to providing products such as meat, milk and eggs, domestic animals will continue to enhance the natural resources base. Nevertheless, there are some environmental concerns related to land quality, in terms of erosion and soil fertility, and animal biodiversity.